PREVALENCE OF INTESTINAL PARASITES AMONG FOOD HANDLERS IN WESTERN IRAN - Kheirandish, Farnaz; Tarahi, Mohammad Javad; Ezatpour, Behrouz (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Parasitic infection is one of the problems that affect human health, especially in developing countries. In this study, all of the fast food shops, restaurants, and roast meat outlets of Khorramabad (Western Iran) and all the staff employed by them, some 210 people, were selected through a census and their stools were examined for the presence of parasites. The parasitological tests of direct wet-mount, Lugol's iodine staining, formaldehyde-ether sedimentation and Trichrome staining techniques were performed on the samples. The data was analyzed with a chi-square test and logistic regression was selected as the analytical model. The results showed 19 (9%) stool specimens were positive for different intestinal parasites. These intestinal parasites included Giardia lamblia 2.9%, Entamoeba coli 4.3%, Blastocystis sp. 1.4%, and Hymenolepis nana 0.5%. There was a significant difference between the presence of a valid health card, awareness of transmission of intestinal parasites, participation in training courses in environmental health with intestinal parasites (p < 0.05). No statistically significant difference was found between the rate of literacy and gender among patients infected with intestinal parasites (p >; 0.05). To control parasitic infection in food handlers, several strategies are recommended such as stool examinations every three months, public education, application of health regulations, controlling the validity of health cards and training on parasitic infection transmission. In this regard, the findings of the present study can be used as a basis to develop preventive programs targeting food handlers because the spread of disease via them is a common problem worldwide.